Sistem Informasi Berbasis Website sebagai Media Edukasi dan Pencegahan Stunting di Posyandu "Mangga" Desa Tumpangkrasak Jati Kudus - Sholikhan, Muhammad; Galeh Septiar Pontang; Fujiama Diapoldo Silalahi (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
"Mangga" Integrated Health Post is one of the Integrated Service Posts located in Tumpangkrasak Village, Jati Subdistrict, Kudus District. There are approximately 80 toddler members who participate in activities every month on the 25th. "Mangga" Integrated Health Post utilizes the home of the health worker as its location, equipped with basic tables and chairs. In broad terms, this dedication aims to (1) Improve services by providing information and education on stunting prevention through the use of a website and (2) Assist in providing facilities such as equipment for "Mangga" Integrated Health Post. The expected outcomes include (1) Publication of articles in a Service Journal. (2) Documentation of activities will be published in the online mass media Jawa Pos Radar Kudus. (3) Publication of photos and videos of activities to be uploaded on the institution's YouTube channel. (4) "Mangga" Integrated Health Post website www.manggahealthpost.com. With website management training, it is possible to enhance the skills of village health workers in developing the "Mangga" Integrated Health Post website, thereby educating residents of the village, especially parents with toddlers, and achieving the goal of stunting prevention.